(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay analyzes the relation between state of detention and constitutional rights linked to health, focusing on the ones that can be recognized as rights of freedom: the claim that no one could prejudice other’s health, but also freedom of therapy, that includes either freedom from obligatory treatments either the possibility to choose between different possible therapies, doctors and treatment centers. Each of these aspects shows, for persons restricted in their personal freedom, many problematics profiles that are examined. To cope with these, sector operators are called to particular and special efforts, in order to made real and concrete the recognition of constitutional rights to restricted persons.